Analisis Produksi Siaran Berita CNN Indonesia Newsroom; Studi Hierarki Pengaruh Level Rutinitas Media - Muh. Yahya Saraka; Lia Amalia (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to determine the production process of the news program CNN Indonesia Newsroom on the CNN Indonesia television channel. What are the pre-production, production, and post-production processes like, and how does the routine level of the media affect the program? The methodology used is a descriptive qualitative approach, and data collection is through observation schemes, documentation, and interviews. This study uses a subjectivism perspective because it wants to know the influence of media routines which are subjective through the Hierarchy of Influence approach introduced by Pamela J. and Stephen D. This research tries to see the influence from the level of media routines, namely, audiences, media organizations, and related news sources. with the news program production process. CNN Indonesia Newsroom goes through three stages of production, namely pre-production, production and post-production. CNN Indonesia Newsroom produces media content according to audience criteria so that it is easy to understand and gain insight from the audience. From the side of media organizations, the influence and intervention of the highest ranks of the media is quite large, which can be seen in planning meetings and editorial meetings. News sources are obtained from reporters' suggestions, the planning team, and program requests. Of these three elements, the influence of audiences and media organizations holds a large portion in determining the media products of the CNN Indonesia Newsroom.